Sales Promotion and Impulse Buying Behavior towards Consumer Goods : The Mediating Role of Purchase Intention - Abdelkhair, Farah Yasin; Babekir, Mamoun Yaseen; Mudawi, Sara Suliman; Al. Abiad, Al. Beisani Al. (Indian Journal of Marketing, 2023)
The purpose of the study was to provide empirical evidence of the purchase intention as a mediator in the relationship between sales promotion and impulse buying behavior of the consumer goods offered by the retailing businesses (hypermarkets, malls, and superstores) in the Kingdom of Saudi Arabia. In this study, the population consisted of the staff members (academicians) working at the King Khalid University in the Tehamat Asir area in the South of the Kingdom. We pretested the questionnaire among 39 academicians. The sample size was set for 220 academicians as reliable shoppers belonging to the University’s academic units spread in different places of Muhayil Asir province, Barig province, and Rejal Alma province. Data were collected using a questionnaire, and only 204 valid and usable questionnaires were analyzed. The results showed that the purchase intention partially mediated the relationship between sales promotion and impulse buying behavior among academicians. This study conclusively showed that the purchase intention served as a construct used by retailers to mediate the relationship between sales promotion and impulse buying behavior of consumer goods. In turn, this might help the retailers design the relevant promotional policies that would urge the consumers’ purchase intention to fall into impulse buying behaviors and promote the retailing business performance.